Separation of phenylalanine transport events by using selective inhibitors, and identification of a specific uncoupler activity in Yersinia pestis. - Smith, P B (1975)
Phenylalanine transport in Yersinia pestis TJW was differentially inhibited by sulfhydryl blocking reagents, uncoupling agents, and respiratory inhibitors. Kinetic studies with potassium cyanide and sodium azide showed that these compounds have no immediate effect on the initial rate of phenylalanine transport, but have an immediate and severe inhibitory effect on the rate of oxygen uptake. Identical studies with p-chloromercuribenzoate (pCMB) and 2,4-dinitrophenol (DNP) showed that these compounds have an instantaneous and total inhibitory effect on phenylalanine transport. DNP stimulated oxygen uptake, and pCMB caused only a sluggish inhibiton of oxygen uptake. pCMB acted as a competitive inhibitor of phenylalanine transport, whereas DNP inhibitied noncompetitively. Arrenius plots of the initial rate of phenylalanine transport in pCMB- and DNP-treated cells showed that DNP alters the transition temperature of the phenylalanine transport system from 17 C for control cells to 12 C. DNP did not inhibit transport when cells were treated at temperatures of 2 to 10 C. PCMB did not alter the normal transition temperature and inhibited phenylalanine transport over a 2 to 30 C temperature range. Efflux induced by both pCMB and DNP were blocked by placing cells at low temperatures (2 to 20 C). Inhibition of adenosine 5'-triphosphate synthesis by DNP did not show any temperature sensitivity as did phenylalanine transport. These data indicate that: (i) respiration is not obligatory for active transport of phenylalanine in Y. pestis TJW; and (ii) pCMB inhibits transport activity by reacting with the sulfhydryl group(s) at the carrier binding site. The data show that the uncoupler, DNP, selectively alters a temperature-dependent property of phenylalanine transport, that is not related to uncoupling activity of DNP , and probably involves membrane lipid alterations.